Compressive strength of ground waste seashells in cement mortars for masonry and plastering - Woon, Chin Peow (2015)
For environmental protection and sustainable development, many research studies have been carried out on the utilization of waste materials in construction such as fly ash, mine tailings, slags, construction and demolition waste, wood sawdust, rice husk ash, crumb rubber and etc. In this study, two types of waste seashells; green mussel and cockle were tested experimentally to replace fine aggregate in cement mortar. The compressive strength of the cement mortar with seashells were compared with those of a control mortar that was made of a conventional river sand. The main parameter of this study was the proportion of ground seashells used as sand replacement (25%, 50%, 75% or 100% by weight). Incorporation of cockle in cement mortar resulted in higher compressive strength as compared to conventional mortar up to 110 percent. However, incorporation of green mussel resulted in decrement in compressive strength by 67 percent. The results indicate that ground seashells can be applied as a sand replacement in mortar mixes and may improve the compressive strength of rendering and plastering mortar.